A relational data model for traditional games / Norhapizah Muda - Muda, Norhapizah (2006)
This research is focused on Malay traditional games in Malaysia. The Malay community has a lot of traditional games which are a legacy from the past. Lack of cultural information especially information about Malay traditional games be the cause difficult to access as it makes it for interested parties the information. No systematically document the traditional games information make it more difficult to access the information. Therefore, the effort to create the database for the Malay traditional games can help Malaysians access the information. It will also be kept safely and there is no need to be concerned that the information will be lost. Methodology used in the research through interview with the expert and also form the journals, books and information from the internet After all information is collected, it will be analyzed to produce the accurate data. The data then, will be use to create a data model for the Malay traditional games.